Respuesta :

solve for 1 variable
actually, simplify the top equation by dividing both sides by 2 first
2g-h=-3

2nd equation
solve for h
add4g both sides
h=13+4g

sub 13+4g for h in other equation


2g-h=-3
2g-(13+4g)=-3
2g-13-4g=-3
-13-2g=-3
add 13 both sides
-2g=10
divide -2
g=-5

sub back
h=13+4g
h=13+4(-5)
h=13-20
h=-7



g=-5
h=-7
solve by substitution
-- h=4g + 13
4g-2(4g+13) = -6
4g- 8g -26 = -6
-4g -26= -6
-4g= 20
g = -5

then plug in value for g into either equation to solve for h
h- 4(-5)= 13
h+20 =13
h= -7